INFLUENCE OF PROBLEM BASED LEARNING MODEL ON STUDENT CREATIVE THINKING ON ELASTICITY TOPICS A MATERIAL - Wartono, W.; Diantoro, M.; Bartlolona, J. R. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2018)
The phenomenon in the classroom where teachers are still limited space to train and to improve students' creative thinking skills (CTS) on the topic of material elasticity is the main reason for this research. Information on improving students' creative thinking skills in material elasticity topics by implementing problem based learning model (PBL) in learning is also limited. Previous research has not revealed any effort related to improving students' creative thinking skills on material elasticity topics by comparing two different learning models. Therefore this study aims to reveal differences in student learning outcomes on material elasticity materials in PBL and conventional models. Based on the research results obtained information that students 'creative thinking skills scores using PBL model is higher compared with that of conventional learning. It also revealed at each meeting that the CTS indicator of students are always improve. It can be concluded that PBL is very effective in training and improving students' creative thinking skill in physics learning. Thus PBL can be recommended in improving students' creative thinking skills.